Typology of Psychological Violence in Maqashid Sharia Perspective - Iffaty Nasyiah; Risma Nur Arifah (Universitas Nurul Jadid, 2024)
Psychological violence in the household is a criminal offense that has not been explained with certainty. The PKDRT Law itself only explains the formulation of the consequences of psychological violence. Thus, it is important to create a typology of this form of psychological violence. This is also the case in Islam. This research aims to analyze the typology of psychological violence from the perspective of maqashid sharia. The type of research used is normative legal research with a conceptual approach. The results show that in the perspective of maqashid sharia, the creation of a typology of psychological violence in the household is a necessity that brings maslahah. In the level of benefit, the determination of this guideline becomes very important and occupies the hajjiyat level because it is related to the need to create convenience in overcoming difficulties. In the context of psychological violence, the difficulty that arises is how to detect the form of psychological violence itself. The creation of guidelines regarding the typology of psychological violence creates legal certainty for perpetrators and victims, realizing justice and legal protection for victims.